Pengolahan Air Limbah Menjadi Air Minum Dengan Menghilangkan Amonium Dan Bakteri E-Coli Melalui Membran Nanofiltrasi - Malikhatul Hidayah (Walisongo Journal of Chemistry, 2018)
Industrial waste water area that flows in the River Flood Canal Semarang can affect the environment if not done processing. Membrane is one alternative water treatment technologies with the principle of filtration. The presence of fouling is a problem encountered in the use of the membrane. In this study will be made of non-fouling nanofiltration membranes made from cellulose acetate. Manufacture of cellulose acetate membrane is accomplished by phase inversion method, which is changing the shape of the polymer solid phase into the liquid phase rich in solvent into solids (membrane) which is rich in polymer. Therefore, the aim of this study was to create a non-fouling nanofiltration membrane using cellulose acetate polymer as well as assess the effect of PEG additives and pre-treatment with UV light to the surface of the structure and performance of cellulose acetate membranes for produced water treatment. Research using cellulose acetate membranes for wastewater treatment is done by varying the type of PEG 1500 and 4000, variations of PEG of 1, 3 and 5% by weight and a UV irradiation for 10, 20 and 30 seconds. The research followed by testing the performance of the membrane in wastewater treatment using a dead-end filtration with the parameters of flux and rejection. Characterization of the membrane was analyzed with SEM and FTIR. Analysis of the results was conducted to determine the levels of turbidity, TDS, COD, Ca2+, S2- and oil in waste water before and after passing through the membrane.